(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The problem of cultural property smuggling is not new to Russia. Every year, a huge amount of cargo is moved across the border of our country, including rare items, publications, etc. Many of these values are an essential component of the cultural wealth of Russia. This study mainly investigates some prevalent issues of criminal legal regulation of smuggling cultural values. To do so, the general scientific research methods within the framework of comparative, logical and statistical analysis are considered. Based on the results obtained, it can be inferred that the criminal law protection of cultural property from illegal transportation across the state border is far from ideal. Hence, it seems crucial to single out the smuggling of cultural property as a separate corpus delicti, including increased liability in the presence of qualifying signs to boost the practice of applying criminal liability for this crime.